2018
DOI: 10.1007/s00213-018-4977-6
|View full text |Cite|
|
Sign up to set email alerts
|

Multi-center, randomized, double-blind, placebo-controlled study of quetiapine extended-release formulation in Japanese patients with bipolar depression

Abstract: RationaleQuetiapine fumarate is an atypical antipsychotic indicated for various mental disorders, but it has not been studied in Japanese patients with bipolar depression.ObjectivesTo evaluate the efficacy and safety of quetiapine XR (extended release) in Japanese patients with bipolar depression.MethodsIn this multi-center, randomized, double-blind, placebo-controlled, fixed-dose study of 431 Japanese adults with bipolar I or II disorder, efficacy was determined by analyzing the mean change from baseline in M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 21 publications
3
30
0
Order By: Relevance
“…The patient characteristics of the initial 8-week double-blind study were described previously [10]. Of the 179 patients receiving 300 mg quetiapine XR in the previous study, 130 patients transitioned into this extension phase.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The patient characteristics of the initial 8-week double-blind study were described previously [10]. Of the 179 patients receiving 300 mg quetiapine XR in the previous study, 130 patients transitioned into this extension phase.…”
Section: Resultsmentioning
confidence: 99%
“…This was a multicenter, open-label, non-controlled extension study to determine the long-term safety and efficacy of quetiapine XR therapy across 98 sites. This study followed on from an 8-week placebo-controlled, double-blind, parallel-group comparative study [10] conducted in Japanese patients with bipolar depression.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In two subsequent RCTs exploring the efficacy and tolerability of quetiapine and active comparators lithium and paroxetine, quetiapine again outperformed placebo in attenuating depressive symptoms while the active comparators did not [9,21]. Placebo-controlled studies of quetiapine extended release (XR) monotherapy have also consistently demonstrated efficacy in bipolar depression [37][38][39]. In terms of relapse prevention, in patients with bipolar I disorder previously stabilised on quetiapine, continued maintenance therapy with quetiapine significantly increases time to recurrence of depressive or manic relapse compared with placebo [40], regardless of any combination with lithium or valproate [41].…”
Section: Quetiapinementioning
confidence: 99%
“…An 8‐week, double‐blind, randomized, placebo‐controlled phase 3 trial of QUEXR was conducted in Japan . This was a fixed‐dose study comparing QUEXR at 300 mg/d (QUEXR300, n = 179), at 150 mg/d (QUEXR150, n = 74), and placebo (n = 177).…”
Section: Introductionmentioning
confidence: 99%